Akuntabilitas Kinerja Bidang Pertamanan DISPERKIM Kota Malang dalam Mewujudkan Good Governance - Rahmaddhana, Febri Herdiansyah; Wike, Wike (Jurnal Ilmiah Administrasi Publik, 2021)
The purpose of this paper is to describe the embodiment of performance accountability in DISPERKIM Parks Sector, Malang City. This paper is also based on the development concept of performance measurement from Speklé & Verbeeten (2014) through three indicators of operational use, incentive use, and explanatory use. The results of this study are: a) Operational use: in organizational operational planning and preparation of budget allocations is strongly influenced by institutional restructuring and the influence of regional heads in determining bureaucratic efficiency; b) Incentive use: the number of employees namely 214 people can only reach the target of 78.45%, so it’s not surprising that Malang City still receives accountability reports in the BB category; and c) Explanatory use: in the formulation of strategy and communication’s goal, the head of the department and the chief of sector are only limited to reviewing every quarter only, meaning there is no subordinate involvement in the formulation of strategy. For strategy and learning management it’s known that Parks Sector minimizes program and activity budgets, so that it’s used as a reference in observing budget absorption